Healthcare. Pleurisy: clinical and diagnostic guidelines, treatment tactics, legal principles - Nevzghoda, Oleksandr; Shapovalova, Viktoriia; Osyntseva, Alina; Shapovalov, Valentyn; Shapovalov, Valerii (Annals of Mechnikov's Institute, 2025)
Introduction. The study is devoted to clinical diagnostic criteria, treatment tactics, and legal aspects of pleurisy management. Along with clinical diagnostic approaches, emphasis is placed on organizational solutions that guarantee continuity of treatment and prevent unjustified prescription of antibacterial drugs. To support clinical decision-making, the organizational and resource tool ABC/VED-analysis was used. Objective. To form a transparent, evidence-based approach to the treatment of pleurisy that integrates clinical diagnostic guidelines, legal principles, and resource planning (ABC/VED). To analyze the structure of costs for pharmacotherapy, to identify critically necessary items for continuity of treatment and to develop a prioritization matrix for antibiotic stock management. Methods. Descriptive-analytical approach with synthesis of modern clinical guidelines and practical algorithms (diagnosis, drainage, antibacterial and intrapleural therapy, surgery), supplemented by ABC/VED analysis of the nomenclature of antibacterial drugs in the context of pleural infection and legal audit of clinical procedures. Results. Clinical-diagnostic guidelines and treatment tactics of pleurisy with the use of antibiotics were outlined. ABC/VED analysis of organizational and resource support was conducted and clinical-pharmacological groups of antibiotics were studied. It was established that the highest costs are incurred by category A drugs (Doramycine, Rovamycin, Unidox Solutab), which are vital and have the highest level of consumption. Category B antibiotics (Spiracin, Cephalexin suspension, Bicillin-3) provide a moderate resource load, while category C (Erythromycin, Doxycycline-Darnitsa) has a minimal economic impact. According to the VED classification, group E costs (Benzylpenicillin, Bicillin-3, Bicillin-5, Penicillin G sodium salt, Cephalexin) dominate, which emphasizes their importance in supporting therapy. Group V includes vital drugs (Doxycycline, Erythromycin, Cephalexin capsules, Unidox Solutab), and group D is formed by reserve drugs (Doramycine, Zinerit, Rovamycin, Spiracin). Matrix analysis confirmed that the greatest resource burden characterizes category A (A/V, A/E, A/D). The results obtained made it possible to classify antibiotics by clinical significance and determine priorities for rationalizing costs. Additionally, legal principles for the diagnosis and treatment of pleurisy, based on the principles of legality, evidence, safety and protection of patients' rights, were formulated. Conclusions. The proposed evidence-based approach synchronizes clinical algorithms for pleurisy management with organizational and resource support (ABC/VED), increasing treatment effectiveness, reducing excessive use of antibiotics, and ensuring the stability of the supply of life-saving drugs. The role of legal principles (informed consent, infection control, documentation, data protection) in the safe and high-quality provision of care is emphasized.